INTERFERON-RIBAVIRIN TREATMENT IN CHRONIC HEPATITIS C- THE LESS TALKED ABOUT ASPECTS - Khalid, Shahid Raza; Khan, Anwaar A; Alam, Altaf; Alam, Altaf; Lak, Nasir Hassan; Butt, Arshad Kamal; Shafqat, Farzana; Alvi, Aftab; Ahmed, Irfan; Sarwar, Shahid; et al. (Journal of Ayub Medical College Abbottabad, 2009)
Background: Combination therapy with interferon and ribavirin has become the standard of care in the treatment of Chronic Hepatitis C (CHC) infected patients. Treatment response, however, is not 100% and is accompanied with side effects faced by the patient as well as observed in haematologic indices. Studies are focusing on daily or high-dose induction therapy with interferon, the titration of interferon dosing to initial viral load, higher doses of interferon throughout treatment, and adjustment of interferon dosing to the viral responses. The safety and efficacy of these approaches have not been sufficiently established. Objectives were to see the response of 2 different dosage regimens, effects and side effects and to assess the efficacy and side effects of 2 treatment regimens of Interferon and Ribavirin in CHC. Methods: A total of 32 patients with CHC at Department of Gastroenterology and Hepatology, Shaikh Zayed Postgraduate Medical Institute Lahore from June 2001 to February 2003 were included in the study and were divided into two groups for treatment. Group A (14 patients) received 5 MU of injection Interferon alpha 2 b S/C daily for 2 weeks followed by 3 MU thrice weekly for the next 22 weeks. Group B (18 patients) received injection interferon alpha 2 b 3 MU S/C thrice weekly for 24 weeks. Ribavirin therapy was started at 1200 mg daily in 3 divided doses and later modified according to side effects. Patients were evaluated at 2, 4, 8, 12, 16, 20 and 24 weeks during the therapy and then 24 weeks after the completion of treatment. Results: Out of 32 adult patients included in the study, 18 were males and 14 females. Haemoglobin was more than 12 gm/dl in females and more than 13 gm/dl in males, WBC count was more than 3.0ï‚´109/L and Platelet count was more than 100ï‚´109/L. Twenty patients completed 6 months combination treatment, 16 reported with their end of treatment HCV RNA PCR results, 8 from each group. Twelve patients were lost to follow up. End of treatment response (ETR) in group A was 88% and 62.5% in group B. Sustained virological response in group-A was 5/8 (62.5%) and 4/5 (50%) in group-B. The frequency and severity of flu like symptoms like fever, body aches, skin rash, hair loss, cough and psychiatric symptoms were more in group A than in group B. There was no significant difference in the 2 groups for haematologic side effects. Conclusions: Treatment with 5 MU interferon daily for initial two weeks followed by 3 MU thrice weekly for 22 weeks is more effective than 3 MU thrice weekly for 24 weeks but with more side effects. Keywords: Hepatitis, Chronic Hepatitis C, Interferon, Ribavirin, Therapy, Side effects